Needs Analysis Of Cognitive Conflict Teaching Materials Integrated with Augmented Reality Global Warming Material - Mustika Hayati; Fatni Mufit (Physics Learning and Education, 2023)
The development of the 21st century is marked by the increasing quality of human resources, especially in the field of science and technology. Conceptual understanding is very important to be improved in the 21st century, this is supported by the goal of an independent curriculum, namely students are able to deepen concepts and strengthen competence. In the independent curriculum, the available teaching materials are still limited, one alternative solution is to develop teaching materials based on cognitive conflict models integrated with Augmented Reality technology on global warming material in order to increase students' conceptual understanding and remediate student misconceptions. This type of research is preliminary research. The instrument used was a questionnaire which was given to 3 teachers at Padang City High School to analyze the implementation of physics learning at school. Then the questionnaire instrument was also given to 130 class X students in two different high schools in Padang City, the aim was to analyze the needs of physics learning devices at school. In addition to the questionnaire, journal analysis was also carried out to analyze high school students' conceptual understanding of global warming material. Data were analyzed quantitatively and qualitatively. Students' conceptual understanding is still low and there are misconceptions about global warming material, which is the result of an analysis of several published journals. In addition, learning in schools is still teacher-centered, teaching materials are still limited, and technology-integrated learning media is also limited. Therefore, from the results of preliminary research it is necessary to develop cognitive conflict-based physics teaching materials that are integrated with augmented reality technology.